Avelumab plus axitinib in unresectable or metastatic type B3 thymomas and thymic carcinomas (CAVEATT): a single-arm, multicentre, phase 2 trial. Issue 10 (October 2022) - Conforti, Fabio; Zucali, Paolo Andrea; Pala, Laura; Catania, Chiara; Bagnardi, Vincenzo; Sala, Isabella; Della Vigna, Paolo; Perrino, Matteo; Zagami, Paola; Corti, Chiara; Stucchi, Sara; Barberis, Massimo; et al.
Summary: Background: Patients with advanced type B3 thymoma and thymic carcinoma resistant to chemotherapy have few treatment options. We report the efficacy and safety results of the combination of the anti-PD-L1 inhibitor avelumab with the anti-angiogenesis drug axitinib in patients with advanced type B3 thymoma and thymic carcinoma. Methods: CAVEATT was a single-arm, multicentre, phase 2 trial, conducted in two Italian centres (the European Instituteof Oncology and the Humanitas Institute, Milan) in patients with histologically confirmed type B3 thymoma or thymic carcinoma, with advanced stage of disease who had progressed after at least one line of platinum-based chemotherapy. Previous treatment with an anti-angiogenesis drug was allowed but not with immune checkpoint inhibitors. Other inclusion criteria were age 18 years or older, an Eastern Cooperative Oncology Group performance status of 0–2, progressive disease, and presence of measurable disease according to Response Evaluation Criteria In Solid Tumours (RECIST) version 1.1. Patients received avelumab 10 mg/kg intravenously every 2 weeks and axitinib 5 mg orally twice daily until disease progression or unacceptable toxicity. The primary endpoint was the centrally assessed overall response rate according to RECIST version 1.1. Patients who received at least one cycle of treatment and had at least one CT scan after treatment start at scheduled time point by protocol were judged assessable for response and were included in efficacy and safety analyses. This study is registered with EUDRACT, 2017–004048–38; enrolment is completed and follow-up is ongoing. Findings: Between April 22, 2019, and June 30, 2021, 32 patients were enrolled. 27 patients had a thymic carcinoma, three a type B3 thymoma, and two a mixed type B3 thymoma and thymic carcinoma. 29 (91%) of 32 patients had stage IVB disease and 13 (41%) of 32 had been pretreated with an anti-angiogenesis drug. 11 of 32 patients had an overall response; thus the overall response rate was 34% (90% CI 21–50); no patients had a complete response, 11 (34%) had a partial response, 18 (56%) had stable disease, and in two patients (6%) progressive disease was the best response. The most common grade 3 or 4 adverse event was hypertension (grade 3 in six [19%] of 32 patients). Four (12%) of 32 patients developed serious adverse events that were new-onset immune-related adverse events, including one grade 3 interstitial pneumonitis, one grade 4 polymyositis, and two grade 3 polymyositis. There were no treatment-related deaths. Interpretation: Avelumab combined with axitinib has promising anti-tumour activity and acceptable toxicity in patients with advanced type B3 thymoma and thymic carcinoma progressing after chemotherapy, and could emerge as a new standard treatment option in this setting. Funding: Pfizer.